Effect and Mechanism of Action of Pushing Method on Rats with Skeletal Muscle Overuse Injury based on Wnt/β-catenin Signaling Pathway - DUAN Miaomiao; HUANG Bo; RUAN Lei; MU Pangpang; CHEN Yiming; PENG Liang (康复学报)
ObjectiveTo observe the effect of pushing method on the repair and regeneration of rats with overuse injury of skeletal muscle, and to explore its mechanism of action based on Wnt/β-catenin signaling pathway.MethodsForty-two rats were selected and divided into blank group, model group and intervention group according to randomized table method, with 14 rats in each group. In addition to the blank group, the model group and intervention group were trained with Armstong centrifugal exercise program to establish a rat skeletal muscle overuse injury model. In the blank and model groups, the right hind limb gastrocnemius muscle and adjacent muscles were coated with petroleum jelly, but no pushing intervention was performed; in the intervention group, the right hind gastrocnemius muscle was pushed (the pressure was about 2 N, the frequency was 80 beats/min, and the intervention was performed once a day in the morning and once a day in the afternoon, lasting for a total of 3 d. The intervention was performed in the right hind limb gastrocnemius muscle for 24 h after the modeling, and in the intervention group for 3 d after the modeling was completed.) The balance beam test was used to assess the motor function of the rats after skeletal muscle injury at 24 h after the end of modeling and 24 h after the end of the intervention, respectively; hematoxylin-eosin staining (HE) method was used to observe the pathological changes of the gastrocnemius muscle; EM-1400 transmission electron microscope was used to observe the ultrastructure of the skeletal muscle fibers; and fluorescence PCR was used to detect the myogenic regulatory factor myogenic differentiation antigen (Myogenic differentiation antigen (MyoD), myogenin (MyoG) and paired box 7 (Pax7) mRNA transcript levels were detected by fluorescence quantitative PCR; MyoD, MyoG, Pax7, Wnt3a, Axin2 and β-catenin protein expression levels were detected by Western blot. Catenin protein expression levels.Results(1) Comparison of motor function：compared with the blank group, the time of passing through the balance beam and the number of times of sliding paw were significantly increased in the model group and intervention group after intervention, and the difference was statistically significant (P<0.05); compared with the model group, the time of passing through the paw and the number of times of sliding paw were significantly decreased in the intervention group after intervention, and the difference was statistically significant (P<0.05). (2) Gastrocnemius muscle histopathological changes：the model group can be seen in the gastrocnemius muscle a large number of myocytes can be seen within the cracks, myogenic fibers fracture; compared with the model group, the degree of damage to the gastrocnemius muscle tissues in the intervention group to reduce the degree of damage, can be seen in the form of myofibers is regular, neatly arranged. (3) Ultrastructural changes in gastrocnemius muscle tissue：local myogenic fiber bundles were broken and dissolved, and a small amount of Z-line structure was dissolved and blurred; compared with the model group, the gastrocnemius muscle cells in the intervention group were slightly edematous, and the structure of the myogenic fiber bundles was clear; part of the myogenic fiber bundles were broken, and the structure of the Z-lines was clear and more neatly arranged. (4) Gastrocnemius muscle tissue MyoD, MyoG and Pax7 mRNA transcript levels：compared with the blank group, MyoD, MyoG and Pax7 mRNA transcript levels were significantly higher in both the model group and the intervention group (P<0.05); compared with the model group, MyoD, MyoG and Pax7 mRNA transcript levels were significantly higher in the intervention group (P<0.05). (5) Gastrocnemius muscle tissue MyoD, MyoG and Pax7 protein expression level：compared with the blank group, MyoD, MyoG and Pax7 protein expression water were significantly higher in both the model group and the intervention group (P<0.05); compared with the model group, MyoD, MyoG and Pax7 protein expression level was significantly higher in the intervention group (P<0.05). (6) Wnt3a, Axin2 and β-catenin protein expression levels in gastrocnemius muscle tissues：compared with the blank group, Wnt3a, Axin2 and β-catenin protein expression levels were significantly higher in both the model group and the intervention group (P<0.05); compared with the model group, Wnt3a, Axin2 and β-catenin protein expression levels were significantly higher in the intervention group (P<0.05).ConclusionPushing method can improve the gastrocnemius muscle injury and motor function in rats with overuse injury model, and its mechanism may be related to the activation of Wnt/β-catenin signaling pathway.